The effects of parameters on the efficiency of DLLME in extracting of PAHs from vegetable samples - Tan Y.H.; Chai M.K.; Wong L.S. (Science Publishing Corporation Inc, 2023)
An effective analytical method based on microwave-assisted extraction (MAE) and dispersive liquid-liquid microextraction (DLLME) followed by gas chromatography-flame ionization detector (GC-FID) was developed for the determination of polycyclic aromatic hydro-carbons (PAHs) in vegetable samples. In most cases, the details of the parameters influencing the efficiency of DLLME in extraction are not well studied. Understanding the reactions of solvents in extraction is the important task on selecting of an appropriate solvent in the process. The effects of parameters affecting the extraction efficiency of DLLME, including extraction solvent and dispersive solvent, extraction time and MAE, such as solvent, microwave power and irradiation time, were studied and explained. The impacts of physio-chemical properties of the selected extraction solvents on the extraction efficiency were also investigated. The results indicated that extraction solvents with low viscosity and low polarity have better extraction efficiency in extraction of PAHs from vegetable sample. No significant difference was observed for the effects of selected dispersive solvents and extraction time on extraction efficiency. In MAE, the types of solvent, microwave power and irradiation time implied some critical effects on the extraction efficiency of DLLME. 2018 Authors.